The Stories of Meibukan Gojyu Ryu Karate as Told by Yagi Meitatsu - Robert Toth (Universidad de León, 2012)
Gojyu-ryu karate has the distinction of being the first of the Okinawan karate styles to be officially named (Higaonna, 1995: 68). Miyagi Chojun created the style and formally registered the name with the Japanese Government in 1933 (Hiagonna, 1985: 28). The late  Yagi Meitoku was Miyagi Chojun's most senior karate student. After Miyagi Chojun's death, the Miyagi family chose Yagi Meitoku to carry on the style's traditions. Yagi taught the system to his two sons. The oldest son, Meitatsu, carries on not only the style's technical finesses and its philosophy, but also the stories that make up its history.